ANALISIS SISTEM ANTRIAN PADA LAYANAN PENGURUSAN PASPOR DI KANTOR IMIGRASI KELAS I SEMARANG - Purina Pakurnia Artiguna; Sugito Sugito; Abdul Hoyyi (Jurnal Gaussian, 2014)
Queue is something that can not be separated in everyday life. Almost all services will form a queue, including passport treatment services at the Immigration Office Class I Semarang.To solve the problems associated with the queue, queuing system model needs to be determined in accordance with the conditions and characteristics queue of the service facility at the Immigration Office Class I Semarang appropriately. So it can be known the measure of system performance to create an effective and efficient service. Based on the data analysis of the six (6) counters work, obtained queuing system model that occurs at the Immigration Office Class I Semarang is, (M/M/2)   queuing model for Passports Taking Counter and Customer Service Counter,  queuing model for file transfer counter and payment transfer counter, and  queuing model for photos counter and interview counter. The effectiveness of the applicant’s passport service process can be determined by calculating the average number of applicants in the system and queue, calculates the average time spent in the system and queue, and calculates the probability of a server that is not serving an applicant. Keywords : Queuing system model, Passport’s services, Size of system performanceANALISIS SISTEM ANTRIAN PADA LAYANAN PENGURUSAN PASPOR  DI KANTOR IMIGRASI KELAS I SEMARANG